Factors influencing Chinese long-term care. (1st January 2012) - Mi, Hong; Yang, Zhenzhen; Zhang, Tiantian
Using the life table and the disability life table, we discuss the relationship between the incidence of disability and the age of the elderly in Jiashan county. It is found that the relationship between age and the incidence of disability can be better illustrated by a sequation rather than by a simple linear equation. Life expectancy, disability-free life expectancy and life-with-disability expectancy all decline with age among the elderly aged ≥60 years while the elderly aged ≥80 years require a relatively long periods of care. Furthermore, the number of the disabled elderly will reach the maximum in 2037, with the majority of people with the age 75 years and older. These data reveal the key population characteristic of the elderly in need of long-term care. It is the information that we should take into account to establish long-term care insurance, along with the lessons from international experience.